Impact of preoperative enteral nutritional support on postoperative outcome in patients with Crohn's disease complicated by malnutrition: Results of a subgroup analysis of the nationwide cohort registry from the GETAID Chirurgie group. (12th March 2021) - Abdalla, Solafah; Benoist, Stéphane; Maggiori, Léon; Zerbib, Philippe; Lefevre, Jérémie H.; Denost, Quentin; Germain, Adeline; Cotte, Eddy; Beyer‐Berjot, Laura; Corte, Hélène; Desfourneaux, Véronique; Rahili, Amine; et al.
Abstract: Aim: Postoperative morbidity is high in patients operated on for Crohn's disease (CD) complicated by malnutrition. This study aimed to evaluate the impact of preoperative enteral nutritional support (PENS) on postoperative outcome in patients with CD complicated by malnutrition included in a prospective nationwide cohort. Method: Malnutrition was defined as body mass index <18 kg/m 2 and/or albuminaemia <30 g/L and/or weight loss >10%. Failure of PENS was defined as the requirement for additional preoperative parenteral nutrition to PENS. Univariate analysis of the risk factors for PENS failure was performed. Propensity score matching (PSM) was used to compare the outcomes between 'upfront surgery' and 'PENS' groups. The primary endpoint was the rate of intra‐abdominal septic morbidity and/or temporary defunctioning stoma. Results: Among 592 patients included, 149 were selected. In the intention‐to‐treat population including 20 (13.4%) patients with PENS failure after PSM, 78 'upfront surgery' and 71 'PENS'‐matched patients were compared, with no significant difference in the primary endpoint. Perforating CD and preoperative intra‐abdominal fistula were associated with PENS failure [37.5 vs 16.1% ( P = 0.047) and 41.2% vs 16.2% ( P = 0.020), respectively]. After exclusion of these 20 patients, PSM was used to compare 45 'upfront surgery' and 51 'PENS'‐matched patients, with a significantly decreased rate of intra‐abdominal septic complications and/or temporary defunctioning stoma in the PENS group (19.6 vs 42.2%, P = 0.016). Conclusion: Preoperative enteral nutritional support is associated with a trend but no conclusive evidence of a reduction in intra‐abdominal septic complications and/or requirement for defunctioning stoma. Patients with perforating CD complicated with malnutrition are at risk of PENS failure.